2022
DOI: 10.1002/erv.2951
|View full text |Cite
|
Sign up to set email alerts
|

We need your ideas—How to deliver developmentally informed treatment and care for emerging adults with eating disorders? A special European Eating Disorder Research issue about age transitions in eating disorders

Abstract: Not all patients suffering from an ED in childhood and adolescence are in need of a transition to an AED service. According to an older publication by Arcelus et al. (2008), approximately one-fourth of a sample of 206 patients with AN cared for by an AED service and aged between 16 and 25 years had had previous involvement with a CAED service. More than half of the former child and adolescent patients had been treated as inpatients and approximately 40% as outpatients. In a more recent study McClelland et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The framework of the interview was based on extensive clinical experience with patients in the transition process and literature research (Herpertz-Dahlmann & Schmidt, 2023). The interview questions were developed in collaboration between the both authors (the English translation of this interview can be found in the supplementary material together with the reflexivity statement).…”
Section: Interviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework of the interview was based on extensive clinical experience with patients in the transition process and literature research (Herpertz-Dahlmann & Schmidt, 2023). The interview questions were developed in collaboration between the both authors (the English translation of this interview can be found in the supplementary material together with the reflexivity statement).…”
Section: Interviewmentioning
confidence: 99%
“…The age at the transfer from a child and adolescent eating disorder service (CAEDS) to an adult service has traditionally been handled more strictly in Anglo‐Saxon countries such as the UK and Australia, as well as in Spain, where patients are asked to move to adult services at the age of 18; however, in other countries such as Italy, France, and Germany (but also currently in most child and adolescent mental health services [CAMHS] in the UK), this transfer is handled more flexibly (for more details, see Herpertz‐Dahlmann & Schmidt, 2023; Winston et al., 2023; Royal College of Psychiatrists, 2017). Patients and parents are often overwhelmed by the transition process; they complain of a lack of information, difficulties in accessing adult services, having too little time for preparation and insufficient support.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…AN affects about 1.4% of young women and girls and 0.2% of boys and men at one point during their lifetime [ 2 ]. The typical onset age is between 14 and 22 years [ 3 ], and clinicians are thus often challenged with the decision of child- vs. adult-centered care, as many healthcare systems clearly distinguish between these services [ 4 ]. For patients treated at a transitional age, e.g., in late adolescence between ages 18 and 20, physicians and therapists may need to evaluate early treatment responses and take decisions with regard to the duration, intensity, and setting of treatment.…”
Section: Introductionmentioning
confidence: 99%